Effects of Relationship Marketing on Customer Retention and Competitive Advantage: A Case Study on Grameen Phone Ltd. - Rahman, S M Asif Ur; Masoom, Muhammad Rehan (Asian Business Review, 2012)
The purpose of this paper is to evaluate whether Relationship Marketing (RM) creates competitive advantage and retains customers for businesses. In order to evaluate RM practices in Grameen Phone (GP), two hundred and sixty five respondents were surveyed. Findings show that GP has been applying RM successfully, consequently retaining customers and achieving competitive advantage. However, GP should emphasize on internal marketing practices and on enhancing employee satisfaction and customer care.